2022
DOI: 10.3390/biology11020256
|View full text |Cite
|
Sign up to set email alerts
|

New CTX-M Group Conferring β-Lactam Resistance: A Compendium of Phylogenetic Insights from Biochemical, Molecular, and Structural Biology

Abstract: The production of extended-spectrum β-lactamases (ESBLs) is the main defense mechanism found in Gram negative bacteria. Among all the ESBLs, the CTX-M enzymes appear as the most efficient in terms of dissemination in different epidemiological contexts. CTX-M enzymes exhibit a striking plasticity, with a large number of allelic variants distributed in several sublineages, which can be associated with functional heterogeneity of clinical relevance. This observational analytical study provides an update of this f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
2
6
0
2
Order By: Relevance
“…The blaCTX-M-1_CV1 and blaCTX-M-1_CV2 subvariants were present in the same species as blaTEM-1_TV2. Previous studies found five key substitutions among CTX-M-1 variants: Val80Ala, Asp117Asn, Ser143Ala, Asp242Gly, and Asn289Asp [43] the first one being consistent with the variants found in this study. This is also the first report for blaOXA-181 detection from non-hospital settings in Ecuador.…”
Section: Discussionsupporting
confidence: 92%
“…The blaCTX-M-1_CV1 and blaCTX-M-1_CV2 subvariants were present in the same species as blaTEM-1_TV2. Previous studies found five key substitutions among CTX-M-1 variants: Val80Ala, Asp117Asn, Ser143Ala, Asp242Gly, and Asn289Asp [43] the first one being consistent with the variants found in this study. This is also the first report for blaOXA-181 detection from non-hospital settings in Ecuador.…”
Section: Discussionsupporting
confidence: 92%
“…The bla CTX-M-1_ CV1 and bla CTX-M-1_ CV2 subvariants were present in the same species as bla TEM-1_ TV2. Previous studies found five key substitutions among CTX-M-1 variants: Val80Ala, Asp117Asn, Ser143Ala, Asp242Gly, and Asn289Asp [42], with the first one being consistent with the variants found in this study. This is also the first report for the detection of bla OXA-181 from a non-hospital environment in Ecuador.…”
Section: Discussionsupporting
confidence: 91%
“…While TEM and SHV types were predominant in the 1980s and 1990s, CTX-M has progressively become the most prevalent ESBL type. CTX-M is further categorized into six phylogenetic groups (CTX-M-1, CTX-M-2, CTX-M-8, CTX-M-9, CTX-M-25, and CTX-M-151) based on amino acid sequence [ 8 ]. CTX-M groups 1 (e.g., CTX-M-1 and CTX-M-15) and 9 (e.g., CTX-M-14 and CTX-M-27) are the most commonly described groups, with CTX-M-15 being the most widespread variant among clinical Enterobacterales worldwide [ 9 ].…”
Section: Introductionmentioning
confidence: 99%